Investigation of Potential Profiles and Influencing Factors of Voice Behavior among Chinese Nurses - Shuangying Huang; Hanwen Chen; Liyan Zhang; Xianming Weng; Lingming Zhou; Xiaoqin Ma; Weiyi Wang (BMC Nursing)
Abstract Background The nursing profession plays a vital role in the provision of healthcare services. The sustainable and high-quality development of nursing work is inseparable from the nurses' proactive voice behavior. However, in China, comprehensive nationwide survey data on nurse voice behavior remains limited. The present study utilized latent profile analysis to examine the potential profiles, current status, and determinants of nurses' voice behavior on a national scale, with the aim of formulating targeted intervention strategies to enhance nurses' capacity for constructive feedback. Methods This study employed a cross-sectional survey design and recruited nurses from medical institutions in China as research participants between November 2023 and January 2024. The survey encompassed three dimensions: individual, environment, and behavior. General demographic questionnaires and voice behavior questionnaires were administered via the questionnaire star platform to collect data for statistical analysis. Results A total of 3528 questionnaires from 552 s-class and three-class hospitals hospitals located in 22 provinces, 4 municipalities, 3 autonomous prefectures and 2 special administrative regions throughout China were collected in this study. By analyzing the potential profile of nurses' voice behavior, three potential categories were formed: low voice behavior group(C1, 21.1% of the total population), medium voice behavior group(C2, 60.9% of the total population), and high voice behavior group(C3, 18.0% of the total population). Factors including night shift work, workload intensity, monthly income, years of nursing experience, professional title, position, health status, personality traits, organizational justice perception, and self-efficacy were found to significantly influence nurses' expression of their opinions. Conclusion The voice behavior of nurses in China exhibits a moderate level. Heterogeneity was observed in the voice behavior of nurses, suggesting variations among individuals. The focus of nurse managers should be on nurses belonging to the C1 and C2 group, enabling them to implement early targeted prevention and care based on the distinctive characteristics and influencing factors associated with each latent profile.